Influence of the shape on the consumers perception of the packaging attributes - Vladić, Gojko; Kecman, Milica; Kašiković, Nemanja; Pál, Magdolna; Stančić, Mladen (Journal of Graphic Engineering and Design, 2023)
Packaging for fast moving consumer goods (FMCG) demands constant attention in order to stay competitive in modern dynamic markets. FMCG consumers do not think about the purchasing product until they enter the place of purchase. This emphasizes importance of the communication in a place of purchase. Alongside promotional banners, displays and counters, packaging can be used for this purpose. While in-store promotional banners, displays and counters represent additional cost, the packaging as the integral part of the product can be used as an important marketing tool that does not add to product cost. Thus packaging becomes an important marketing tool that does not add to product cost. Marketers, distributors and researchers as well must take into consideration the complexity of consumer behaviour to achieve desired results. Alongside graphic design, material, colour, etc. packaging shape is considered as an important tool for product differentiation and promotion. Having this in mind, it is unclear why the influence of the packaging shape on the consumer remains the least examined of all packaging characteristics. The aim of this research is to understand the influence of packaging shape design on the consumer’s perception. The survey study conducted among the consumers of the fast moving consumer goods gave clear insight into the influence of packaging shape on the perception of packaging characteristics. The results can help to improve packaging shape design in order to achieve better market impact.